2022
DOI: 10.1002/jmv.27989
|View full text |Cite
|
Sign up to set email alerts
|

Relevant SARS‐CoV‐2 viremia is associated with COVID‐19 severity: Prospective cohort study and validation cohort

Abstract: Background Early Kinetics of SARS‐CoV‐2 viral load (VL) in plasma determined by quantitative RT‐PCR was evaluated as a predictor of poor clinical outcome in a prospective study and assessed in a retrospective validation cohort. Methods Prospective observational single‐centre study including consecutive adult patients hospitalised with COVID‐19 between November 2020 and January 2021. Serial plasma samples were obtained until discharge. Quantitative RT‐PCR was performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…AUC viraemia efficiently predicted COVID‐19 outcome, with a fourfold increased risk in severity and a fivefold increased risk of death when AUC viraemia was above the defined thresholds. These results add to the growing body of literature indicating that detectable levels of SARS‐CoV‐2 transcripts in plasma are associated with COVID‐19 severity 4,31–34 . Recent studies reported that infectious virus is usually not recovered from the plasma of viraemic SARS‐CoV‐2 infected individuals, 31,35 suggesting that detection of viral RNA in plasma likely results from the translocation of viral products from the lungs into the blood, rather than from the systemic replication of SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…AUC viraemia efficiently predicted COVID‐19 outcome, with a fourfold increased risk in severity and a fivefold increased risk of death when AUC viraemia was above the defined thresholds. These results add to the growing body of literature indicating that detectable levels of SARS‐CoV‐2 transcripts in plasma are associated with COVID‐19 severity 4,31–34 . Recent studies reported that infectious virus is usually not recovered from the plasma of viraemic SARS‐CoV‐2 infected individuals, 31,35 suggesting that detection of viral RNA in plasma likely results from the translocation of viral products from the lungs into the blood, rather than from the systemic replication of SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 54%
“…These results add to the growing body of literature indicating that detectable levels of SARS‐CoV‐2 transcripts in plasma are associated with COVID‐19 severity 4,31–34 . Recent studies reported that infectious virus is usually not recovered from the plasma of viraemic SARS‐CoV‐2 infected individuals, 31,35 suggesting that detection of viral RNA in plasma likely results from the translocation of viral products from the lungs into the blood, rather than from the systemic replication of SARS‐CoV‐2. Hence, single viral load measures, but more importantly, total exposure as measured by AUC in our study, are likely to reflect the degree of lung insult, which may explain their positive predictive values for disease severity.…”
Section: Discussionmentioning
confidence: 54%
“…They replicate predominantly in local mucosal tissue, without causing viremia, and do not significantly encounter the systemic immune system or the full force of adaptive immune responses, which take at least 5–7 days to mature, usually well after the peak of viral replication and onward transmission to others. SARS-CoV-2 “RNAemia” (circulation of viral RNA in the bloodstream, as is seen with most mucosal respiratory virus infections, as distinct from viremia, in which infectious viruses can be cultured from the blood), has been reported, and RT-PCR levels of viral RNA have been linked to severe disease, 23 , 24 similar to studies of influenza RNAemia. 25 , 26 As a result, the non-systemically replicating respiratory viruses, apparently including SARS-CoV-2, 13 , 14 , 15 tend to repeatedly re-infect people over their lifetimes without ever eliciting complete and durable protection.…”
Section: Introductionmentioning
confidence: 83%
“…This has not only proved essential from a practical standpoint, it is also reasonable biologically, as infection is the result of the interaction of the virus with the surface of the mucosa, while death is the result of the massive proliferation of the virus throughout the body, as has been made clear by recent autopsy and virological studies. 28,29 It has been argued, and admirably supported by laboratory study, that vaccine protection against infection is principally accomplished by B-cells, and the antibodies that they make, while vaccine protection against death is principally accomplished by T-cells, and the cell-mediated responses that they make. 30 As noted above, Cellular Phylodynamic math gives us a chance to track COVID-19 Lethality and COVID-19 Infectivity to the T-and B-cells that affect virus impact and count how they change upon immunization.…”
Section: Different Vaccines Have Different Reductions In Covid-19 Inf...mentioning
confidence: 99%